Evaluation of The Chloroquine and Resveratrol Combination in Inhibiting β-Hematin Formation In Vitro - Faizal Hermanto; Sri Wahyuningsih; Risky Zamzami Adnan (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Malaria, caused by the Plasmodium parasite, remains a significant global health issue, exacerbated by drug resistance. This study aimed to explore the potential of combining chloroquine (CQ) and resveratrol in inhibiting β-hematin formation, a key process in the parasite's detoxification mechanism. The research began with the preparation of various concentrations of CQ and resveratrol, which were then combined and tested for their effects on inhibiting β-hematin in vitro using an ELISA reader. The results showed that both CQ and resveratrol individually inhibited β-hematin formation at moderate levels. However, their combination demonstrated a significant increase in inhibition, with the most effective combination being CQ at 164.03 μM and resveratrol at 0.98 μM. Statistical analysis confirmed that this combination was far more effective than using each compound separately. The study concluded that the combination of CQ and resveratrol can enhance the inhibition of β-hematin formation, providing a promising approach to improving malaria treatment efficacy, especially in the face of increasing drug resistance.